Writing the personal : getting your stories onto the page - Faulkner, Sandra L.; Squillante, Sheila (Teaching writing (Sense Publishers), 2016)
The Teaching Writing series publishes user-friendly writing guides penned by authors with publishing records in their subject matter. Through detailed exercises, exemplars, and a breakdown of the key elements and considerations of personal writing, Faulkner and Squillante provide a lively introduction and guide for writers to the art and craft of personal writing. Their conversational tone about audience, point of view, form, structure, ethics, research, and finding and making time for writing practice is a not-to-miss primer and reference. This book is appropriate for classes focused on poetry, creative nonfiction, ethnography, qualitative research, memoir, narrative inquiry, and other types of life writing, as well as individual writers honing their craft. Writing the Personal invites us all to find our stories and instructs us how to shape them for an audience and for ourselves. "Writing the Personal is the ideal book for anyone interested in exploring his or her life through writing. It is a must-read for any writer serious about deepening her understanding of craft."--Kate Hopper, author of Ready for Air and Use Your Words and co-author of Silent Running. "A focus on techniques makes this a useful book to read straight through or equally to dip in and out of according to your personal tastes. However you come to the recipes offered in this clever cookbook, you're sure to enjoy the feast inside."--Stacy Holman Jones and Anne Harris, co-authors of Writing for Performance. "Faulkner and Squillante seamlessly collaborate to each bring their unique and varied writing backgrounds and academic credentials to this text to create a unique and invaluable book."--Bernadette Marie Calafell, University of Denver, author of Monstrosity, Performance and Race in Contemporary Culture. "Faulkner and Squillante are skillful, honest, and generous teachers of the craft."--Dinty W. Moore, author of The Mindful Writer: Noble Truths of the Writing Life. "In this innovative and inspiring book, Faulkner and Squillante offer practical advice about writing personal stories."--Tony E. Adams, Northeastern Illinois University. Sandra L. Faulkner teaches, writes poetry, and researches about close relationships at Bowling Green State University in NW Ohio. Sheila Squillante is a poet and essayist living in Pittsburgh and teaching in the MFA program at Chatham University.